2020
DOI: 10.3390/genes11030324
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptomic Analysis Reveals a Regulatory Network of Oxidative Stress-Induced Flowering Signals Produced in Litchi Leaves

Abstract: Litchi is an important subtropical fruit tree that requires an appropriately low temperature to trigger floral initiation. Our previous studies have shown that reactive oxygen species (ROS) are involved in litchi flowering. To identify oxidative stress-induced flowering related genes in leaves, 'Nuomici' potted trees were grown at medium low-temperature conditions (18/13 • C for day/night, medium-temperature). The trees were treated with the ROS generator methyl viologen dichloride hydrate (MV) as the MV-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The potential target‐function proteins of these three genes were identified as DRGs at 8–20 HAT, which mainly enriched with genes involved in ‘glycogen biosynthetic process’, ‘lipid metabolic process’, ‘sucrose metabolic’, and ‘glutathione metabolic process’. When drought treatment was extended to 8 h, SiWRKY049 , SiWRKY062 , and SiWRKY018 (Muthamilarasan et al., 2015), which might be involved in flowering, similar to their homologs in Arabidopsis (Jue et al., 2018; Lu et al., 2020), were all significantly downregulated. We found that the potential target‐function proteins related to the petal bloom‐ and pollen tube elongation‐related term ‘microtubule‐based movement’ were also identified as DRGs at 8 HAT (Figure 2c and Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The potential target‐function proteins of these three genes were identified as DRGs at 8–20 HAT, which mainly enriched with genes involved in ‘glycogen biosynthetic process’, ‘lipid metabolic process’, ‘sucrose metabolic’, and ‘glutathione metabolic process’. When drought treatment was extended to 8 h, SiWRKY049 , SiWRKY062 , and SiWRKY018 (Muthamilarasan et al., 2015), which might be involved in flowering, similar to their homologs in Arabidopsis (Jue et al., 2018; Lu et al., 2020), were all significantly downregulated. We found that the potential target‐function proteins related to the petal bloom‐ and pollen tube elongation‐related term ‘microtubule‐based movement’ were also identified as DRGs at 8 HAT (Figure 2c and Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) can be produced when DNA replication is blocked [ 46 ]. ROS are considered to be signaling molecules in response to stress [ 47 ], not only affecting cell proliferation and size, but also promoting plant flowering through promoting expression of the flowering genes FT1 and FT2 in litchi leaves [ 48 , 49 ]. Besides, eukaryotic polymerase plays a key role in maintaining genomic stability; for example, Arabidopsis polymerase α ensures the stable maintenance of repressive histone modifications, and flowering genes FT and AG are upregulated because of loss of H3K27me3 in the DNA polymerase α mutant [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MV treatment induces senescence and leaf abscission in litchi (Yang, Kin, et al., 2018). In contrast, DMTU is a ROS scavenger that has also been used in litchi (Lu et al., 2020). Therefore, at 30 days after anthesis, 30 fruitlets with peduncle as a biological replicate were collected and instantly cultured in 50‐ml tubes with MV (20 μ m MV), DMTU (10 m m DMTU), or control solution, respectively (see an overview of experimental set‐up in Figure S1).…”
Section: Methodsmentioning
confidence: 99%